Comprehensive assessment of spatial quality in traditional village landscapes of the Yuanshui River Basin using semantic differential and Entropy Weight Methods - Wang, Lie; Zhuang, Ji’an; Wang, Mo; Adnan, Rana Muhammad (Frontiers in Environmental Science, 2025)
The Yuanshui River Basin’s traditional villages face significant threats of degradation and homogenization due to rural construction, suburban expansion, and agricultural modernization, endangering their cultural heritage, agrarian identity, and ecological diversity. This study proposes a robust framework for evaluating the spatial quality of traditional village landscapes, combining the Semantic Differential (SD) method with the Entropy Weight Method (EWM). Six core landscape components—traditional architecture, water bodies, roads, agricultural areas, vegetation, and environmental psychological landscapes—were analyzed. Subjective perceptions were captured through structured surveys and interviews, utilizing carefully designed semantic differential scales. Statistical analysis demonstrated high reliability (Cronbach’s α = 0.747) and validity (KMO = 0.836; Bartlett’s test of sphericity, p < 0.001). The entropy weights ranked the landscape components as follows: traditional architectural landscape (2.429), environmental psychological landscape (2.183), vegetation landscape (2.159), waterbody landscape (1.530), agricultural landscape (1.522), and road landscape (1.052). Regression analysis revealed a strong correlation between the SD and EWM methods (SD = −1.284 + 7.622EWM), and the average SD score (0.787) reflected favorable spatial quality in the basin’s traditional villages. The results highlight tranquility, abundant vegetation, layered plant structures, and natural aesthetics as critical elements of spatial quality. These findings provide valuable insights for landscape conservation strategies and rural policy development.